Clinical and pathological features of intraductal papillary neoplasm of the biliary tract and gallbladder. Issue 9 (September 2015) - Bennett, Sean; Marginean, E. Celia; Paquin‐Gobeil, Melanie; Wasserman, Jason; Weaver, Joel; Mimeault, Richard; Balaa, Fady K.; Martel, Guillaume
Abstract Background Intraductal papillary neoplasms of the biliary tract (IPNB) and intracholecystic papillary neoplasms (ICPN) are rare tumours characterized by intraluminal papillary growth that can be associated with invasive carcinoma. Their natural history remains poorly understood. This study examines clinicopathological features and outcomes. Methods Patients who underwent surgery for IPNB/ICPN (2008–2014) were identified. Descriptive statistics and survival data were generated. Results Of 23 patients with IPNB/ICPN, 10 were male, and the mean age was 68 years. The most common presentations were abdominal pain (n = 10) and jaundice (n = 9). Tumour locations were: intrahepatic (n = 5), hilar (n = 3), the extrahepatic bile duct (n = 8) and the gallbladder (n = 7). Invasive cancer was found in 20/23 patients. Epithelial subtypes included pancreatobiliary (n = 15), intestinal (n = 7) and gastric (n = 1). The median follow‐up was 30 months. The 5‐year overall (OS) and disease‐free survivals (DFS) were 51% and 57%, respectively. Decreased OS (P = 0.09) and DFS (P = 0.05) were seen in patients with tumours expressing MUC1 on immunohistochemistry (IHC). Conclusion IPNB/ICPN are rare precursor lesions that can affect the entire biliary epithelium. At pathology, the majority of patients have invasive carcinoma, thus warranting a radical resection. Patients with tumours expressing MUC1 appear to have worse OS and DFSs.